2002
DOI: 10.1081/agb-120013321
|View full text |Cite
|
Sign up to set email alerts
|

On Varieties of Groups Without Positive Laws

Abstract: We give negative answers to three questions concerning positive laws and A p A varieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The negative answer to the problem is given in [12]. It is shown that there exists a group G which contains a free non-abelian subsemigroup (hence it has no positive laws), while var(G) does not contain A p A for any p. This group G is the finitely generated relatively free group, which is studied in Chapter 9 of [20].…”
Section: Theorem 4 An N-engel Group G Satisfies a Positive Law If G Imentioning
confidence: 99%
“…The negative answer to the problem is given in [12]. It is shown that there exists a group G which contains a free non-abelian subsemigroup (hence it has no positive laws), while var(G) does not contain A p A for any p. This group G is the finitely generated relatively free group, which is studied in Chapter 9 of [20].…”
Section: Theorem 4 An N-engel Group G Satisfies a Positive Law If G Imentioning
confidence: 99%